Gender Differences in Body Evaluation: Do Men Show More Self-Serving Double Standards Than Women? - Voges, Mona M.; Giabbiconi, Claire-Marie; Schöne, Benjamin; Waldorf, Manuel; Hartmann, Andrea S.; Vocks, Silja (Frontiers in Psychology, 2019)
Generally speaking, compared to women, men are less dissatisfied with their own body and consider themselves to be better-looking and less overweight. So far, however, it is unclear whether these divergent body ratings arise from the application of double standards. With the present study, we examined whether men apply different standards to their own body than to other men’s bodies and whether they differ from women in this regard. To this aim, we presented n = 104 women and n = 93 men with pictures of thin, average-weight, overweight, athletic and hypermuscular male and female bodies on a computer screen. To manipulate identification, we showed the bodies of the respective participant’s gender once with the participant’s own face and once with the face of another person. Identity cues, such as faces, might activate different body schemata, which influence body ratings and thus lead to the application of double standards. Participants were instructed to rate their emotional reaction to the bodies according to valence and arousal, and to rate the bodies with respect to attractiveness, body fat, and muscle mass. The application of double standards was determined by calculating the difference between the rating of a body presented with the participant’s face and the rating of the same body presented with another person’s face. Both women and men showed self-deprecating double standards in valence, body attractiveness, body fat and muscle mass for the overweight body. Men also revealed self-deprecating double standards for the thin, average-weight and hypermuscular bodies, but evaluated the athletic body as more attractive and with a higher positive feeling when it was presented with their own face. Women did not show any self-serving double standards and showed fewer self-deprecating double standards than men. The results indicate that men devalue non-ideal bodies and upvalue ideal bodies when they are self-related, whereas women more rate in a fair-minded manner. Thus, in contrast to women, an advantage for men may be that they are able to self-enhance in the case of desirable bodies. This ability to self-enhance regarding desirable features might be beneficial for men’s self-worth and body satisfaction.